THE POLITENESS STRATEGY USED BY SHERLOCK HOLMES IN THE SIGN OF FOUR NOVEL - Evi Pebri Ila Rachma; Shofi Nur Aziizah (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2025)
This study aims to analyze politeness strategy used by Sherlock Holmes in Arthur Conan Doyle's novel The Sign of Four, along with the social factors that influence their use. The research uses a qualitative method, with the researcher serving as the main instrument. Data are collected by examining the dialogues involving Sherlock Holmes in the novel that contain politeness strategies. The analysis applies Brown and Levinson’s (1987) theory to identify the types of strategies used and the social factors influencing them. The analysis results show 81 data of bald on record strategies, 116 data of positive politeness strategies, 53 data of negative politeness strategies, and 7 data of off record strategies. The social factor analysis reveals 218 data of social distance and 39 data of power, while no data are found for the level of imposition.